Perceptions towards attitude of rural leaders towards some agricultural technologies in Malaysia paddy farming - Masso, Wisam Yako Aziz; Man, Norsida; Mohd Nawi, Nolila (European Centre for Research Training and Development, United Kingdom, 2016)
Paddy is the primary staple food crop. In Malaysia there are 0.3 million paddy farmers in Malaysia. The farm sizes of 65% of general paddy farmers are underneath one hectare. As the rural leaders play a function in important programs in agricultural extension. However, the study was conducted to determine the attitude of rural leaders towards Some Agricultural Technologies In Malaysia Paddy Farming, and explore the relationship between the selected characteristics of the respondents. Data were collected through personal interview from 260 randomly selected in MADA area. District during April to June 2015. A five point Likert scale was used to determine the attitude of rural leaders. The majority (57.7%) of the respondents had a moderate level of attitude. The correlation analysis between socio-demographic characteristics and attitude statements show that there is a positive and significant relationship between variable occupation attitudinal statements, and a negative relationship was also found to exist between the paddy income and the respondent’s attitude at 0.05 level of significance.